1993
DOI: 10.1002/cber.19931260130
|View full text |Cite
|
Sign up to set email alerts
|

Sterically Congested Molecules, 6. Lone Electron Pair Donor Quality of the Imino Function: Increased Front Strain and Electronic Substituent Effects on Sterically Accelerated Nitrogen Inversion in Iminocyclopentanes

Abstract: The p-substituents of 2,6-dimethyl-N-(2,2,5,5-tetramethylcyclopenty1idene)anilines are modified without interfering reactions at the CN double bond. The resultant series (5-8, lO -19) shows a strong (ca. -4.7 kcal/mol) steric acceleration of (EIZ) diastereotopomerization by front strain along the CN double bond but also the usual electronic substituent dependence, characterized by a Hammett op correlation (e = + 2.7). Conversely, the substituent constant for lithium at the p-position of 7 may be estimated. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…−22.9 – (−11) ≈ −12 cal mol –1 K –1 is instructive: That entropic penalty may have to do more with Li + (THF) 4 migration than with the lateral motion ( 19 → 20 ) of α-aryl in Scheme . This expectation is based on observations , of practically zero activation entropies for the sp 2 -stereoinversion of the lone electron pair at nitrogen in the Schiff base families 23 and 24 (Scheme ). If the ground states and diastereotopomerizations of 23 and 23 ′ can be taken as isoelectronic models for the carbanion parts of 19 and 19 ′ in the absence of lithium, it may be concluded that the lateral motion of α-aryl alone toward sp-hybridization as in 20 would not necessarily create a strong contribution to the activation entropy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…−22.9 – (−11) ≈ −12 cal mol –1 K –1 is instructive: That entropic penalty may have to do more with Li + (THF) 4 migration than with the lateral motion ( 19 → 20 ) of α-aryl in Scheme . This expectation is based on observations , of practically zero activation entropies for the sp 2 -stereoinversion of the lone electron pair at nitrogen in the Schiff base families 23 and 24 (Scheme ). If the ground states and diastereotopomerizations of 23 and 23 ′ can be taken as isoelectronic models for the carbanion parts of 19 and 19 ′ in the absence of lithium, it may be concluded that the lateral motion of α-aryl alone toward sp-hybridization as in 20 would not necessarily create a strong contribution to the activation entropy.…”
Section: Resultsmentioning
confidence: 99%
“…1 H NMR (400 MHz, THF, 25 °C) δ 1.32 (s, 3 H, 1 × 1-CH 3 ; second 1-CH 3 not detected), 1.42 and 1.46 (2 s, 2 × 3 H, 2 × 3-CH 3 ), 1.93 (s, 3 H, 6′-CH 3 ), (2′-CH 2 Li not detected), 5.44 (d, 3 J = 7.0 Hz, 1 H, 5′-H), 6.00 (s, 1 H, α-H), 6.11 (d, 3 J = 8.0 Hz, 1 H, 3′-H), 6.26 (t, 3 J = 7.6 Hz, 1 H, 4′-H), 7.07 (m, 4 H, 4-/5-/6-/7-H), assigned through comparison of the lithiation shifts Δδ (Table 1) with those of benzyllithium; 16 13 C NMR (100.6 MHz, THF, 25 °C) δ 21.9 (6′-CH 3 ), 29.7 and 30.1 (2 × 1-CH 3 ), 32.3 and 33.4 (2 × 3-CH 3 ), 38.4 (2′-CH 2 Li), 47.6 (C-1), 47.9 (C-3), 106.5 (C-5′), 115.1 (C-3′), 121.3 (C-1′), 122.7 (C-7), 122.9 (C-4), 126.0 (C-α), 126.6 (C-5), 126.7 (C-6), 127.1 (C-4′), 133.8 (C-6′), 150.1 (C-9), 153.1 (C-8), 156.0 (C-2′), 157.9 (C-2), assigned through comparison with 11 and as above with Δδ of benzyllithium. 15 2-[α-(1,1,3,3-Tetramethyl-2-indanylidene)benzyl]adamantan-2-ol (25). Prepared from 3 with adamantan-2-one in Et 2 O; mp 160.5−162 °C (pentane); 1 H NMR (400 MHz, CDCl 3 , 25 °C) δ 0.98 (broadened s, 6 H, 2 × 1-CH 3 ), 1.48 (d, 2 J ≈ 12 Hz, 4 H, 1 × 4″-H, 1 × 8″-H, 1 × 9″-H, and 1 × 10″-H), 1.64 (broad t, 3 J ≈ 3 Hz, 2 H, 2 enantiotopic 6″-H), 1.74 (m, 3 J ≈ 3 Hz, 1 H, 5″-H), 1.76 (s, 6 H, 2 × 3-CH 3 ), 1.78 (m, 3 J ≈ 3 Hz, 1 H, 7″-H), 1.83 (broad d, 2 J ≈ 12 Hz, 2 H, 1 × 8″-H and 1 × 10″-H), 2.30 (broad d upon broad m, 2 J ≈ 12 Hz, 4 H, 1 × 4″-H and 1 × 9″-H upon 1″-/3″-H), 6.98 (dm, 3 J = 7.5 Hz, 1 H, 7-H), 7.13 (dm, 3 J = 7.5 Hz, 1 H, 4-H), 7.16 (td, 3 J = 7.2 Hz, 1 H, 6-H), 7.21 (td, 3 J = 7.2 Hz, 1 H, 5-H), 7.24 (partially hidden t, 3′-/5′-H), 7.25 (hidden, 4′-H), 7.35 (dm, 2 H, 2′-/6′-H), assigned through SCS, 20 comparison with 2-tert-butyladamantan-2-ol, 33 and the NOESY correlations 2′-/6′-H ↔ 3′-/5′-H ↔ 1-CH 3 (w, no crosspeaks with adamantyl signals), 6-H ↔ 7-H ↔ 1-CH 3 ↔ 2′-/6′-H ↔ 8″-/10″-H (at δ = 1.83) ↔ 8″-/10″-H (at δ = 1.48), and 5-H ↔ 4-H ↔ 3-CH 3 ↔ 1″-/3″-H ↔ 4″-/9″-/8″-/10″-H (at δ = 1.48) ↔ (5″-/ 7″-H) ↔ 6″-H; 1 H NMR (400 MHz, CDCl 3 , −63 °C) δ = 0.50 (broadened s, 3 H, 1 × 1-CH 3 ), 1.42 (s, 3 H, 1 × 3-CH 3 ), 1.60 (s, 3 H, 1 × 1-CH 3 ), 1.62 (not resolved, 2 H, 2 × 6″-H), 1.76 (1 H, 5″-H), 1.80 (1 H, 7″-H), 1.96 (s, 3 H, 1 × 3-CH 3 ), 3.33 (s, 1 H, OH), 7.05 (1 H, 7-H), 7.44 (very broad, 1 × 2′-/6′-H); 13 C NMR (100.6 MHz, CDCl 3 , 25 °C) δ 26.1 (dm, 1 J = 132 Hz, C-5″), 26.7 (dm, 1 J = 132 Hz, C-7″), 31.3 (sharp qq, 1 J = 127 Hz, 3 J = 4.5 Hz, 2 × 3-CH 3 ), 32.7 (broad q, 1 J = 127 Hz, 2 × 1-CH 3 ), 33.4 (t, 1 J = 128 Hz, C-4″/-9″), 35.3 (t, 1 J = 128 Hz, C-8″/-10″), 36.2 (d, 1 J = 132 Hz, C-1″/-3″), 37.4 (t, 1 J ≈ 130 Hz, C-6″), 48.1 (unresolved, C-3), 51.0 (m, C-1), 79.9 (broad, C-2″), 122.0 (dd, 1 J = 156 Hz, 3 J = 7.5 Hz, C-7), 122.2 (dd, 1 J = 157 Hz, 3 J = 7.5 Hz, C-4), 125.8 (dd, 1 J = 159 Hz, 3 J ≈ 7.5 Hz, C-3′/-5′), 126.4 (dt, 1 J = 159.5 Hz, 3 J = 7.5 Hz, C-4′), 126.6 (dd, 1 J = 159.5 Hz, 3 J = 7.5 Hz, C-5), 126.9 (dd, 1 J = 159 Hz, 3 J = 7.5 Hz, C-6), 132.3 (dt, 1 J = 159 Hz, 3 J = 6.5 Hz, C-2′/-6′), 140.7 (t, 3 J ≈ 7 Hz, C-1′), 145.1 (unresolved, C-α), 148.8 (broad, C-8), 151.6 (broad, C-9), 157.7 (unresolved, C-2), assigned through SCS, 20 comparison with 2tert-butyladamantan-2-ol, 33 and 13 C/ 1 H heterocorrelation (HSQC); 13…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…It is obvious from molecular models (and verified by Xray analysis [31) that the aryl group of 4h has to prefer a nearly orthogonal arrangement with respect to the CN double bond, as shown in 12/13. This is also the most suitable conformation for the lone electron pair to interact with the aromatic 7c system.…”
Section: Electrophilic Aromatic Substitution Activated By Sp2-nitmentioning
confidence: 94%
“…From 1-propano1200 mg (35%) of 5c with m.p. 185-187.5"C. -IR (KBr): 0 = 2960 cm- ', 2875,2470 (br), 1965 (br) C 72.96 H 9.36 N 5.01 Found C 73.72 H 9.41 N 5.16 N-Methyl-N-(2,5,5-trimethyl-l-cyclopenten-l-yl)aniline (6): N-(Cyclopenty1idene)aniline was prepared (33%) from cyclopentanone diethyl acetal ["] and aniline in the presence of anhydrous ZnC1, according to the literature method ['31; T / 1 0 Torr). It was then subjected to four deprotonation and methylation cycles according to the G P to yield exclusively the crude enamine 6, which was not basic and was not 2,6-Dimet hyl-l-nitro-N-(2,2,5,5-tetramethylcyclopentylidene)aniline (12): 12 ml of conc.…”
Section: 6-dimethyl-n-(2-methylcyclopentylidene)aniline (4c)mentioning
confidence: 99%